New dissertations in mathematics education by doctoral students in the Nordic Graduate School - Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2006)
As I wrote in the issue 3-4 of Nomad in 2005, the year 2006 will be exceptional because of the number of doctoral students who will finish their research education in mathematics didactics and defend their dissertations. Already in the first quarter of the year there have been at least five dissertations printed and made public. A short presentation of them will be made here, as they are likely to be of interest to the whole Nordic Graduate School and many Nordic researchers.